2020
DOI: 10.1186/s13756-020-00842-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating antimicrobial appropriateness in a tertiary care pediatric ICU in Saudi Arabia: a retrospective cohort study

Abstract: Background Inappropriate antibiotic utilization is associated with the emergence of antimicrobial resistance (AMR) and a decline in antibiotic susceptibility in many pathogenic organisms isolated in intensive care units. Antibiotic stewardship programs (ASPs) have been recommended as a strategy to reduce and delay the impact of AMR. A crucial step in ASPs is understanding antibiotic utilization practices and quantifying the problem of inappropriate antibiotic use to support a targeted solution. We aim to chara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…Glycopeptide use among PICUs (98 DOT/1000pd) was more than three-times higher than glycopeptide use among non-ICU wards (30 DOT/1000pd); this is likely due in part to more frequent use of central lines and coverage for coagulase negative staphylococci on PICUs. Glycopeptide use among PICUs in this study was similar to use on a German PICU (90 DOT/1000pd) [56], but lower than Brazilian, Saudi Arabian and South African PICUs (151 to 263 DOT/1000pd) [52,[54][55][56]. Differences in glycopeptide use may be partially due to differences in rates of methicillin-resistant Staphylococcus aureus across jurisdictions [56].…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Glycopeptide use among PICUs (98 DOT/1000pd) was more than three-times higher than glycopeptide use among non-ICU wards (30 DOT/1000pd); this is likely due in part to more frequent use of central lines and coverage for coagulase negative staphylococci on PICUs. Glycopeptide use among PICUs in this study was similar to use on a German PICU (90 DOT/1000pd) [56], but lower than Brazilian, Saudi Arabian and South African PICUs (151 to 263 DOT/1000pd) [52,[54][55][56]. Differences in glycopeptide use may be partially due to differences in rates of methicillin-resistant Staphylococcus aureus across jurisdictions [56].…”
Section: Discussionmentioning
confidence: 46%
“…A large study of billing data from 41 PICUs in the United States reported a median-adjusted rate of 1043/1000pd in 2010–2014 [ 45 ]. Studies from Saudi Arabia in the mid-2010s found AMU rates among PICUs between 697 and 849 DOT/1000pd [ 54 , 55 ]. A German intervention study found an AMU rate of 1226 DOT/1000pd [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a larger study conducted in the USA included 41 PICUs and reported a median antibiotic exposure of 104.3 DOT/100pd in 2010–2014 [ 22 ]. In a single-centre study conducted in Saudi Arabia in 2017, antibiotic consumption in PICU patients was found to be 84.9 DOT/100pd [ 33 ], while a similar study conducted in South Africa in 2015 revealed a rate of 113.7 DOT/100pd [ 8 ]. The mentioned studies showed large-scale differences in prescribing patterns that might arise from differing demographic characteristics, from variations in infectious diseases and resistance patterns, and from the availability of AMS programs: some institutions might have well-developed programs while others seem to lack effective ones [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies conducted among ICU sepsis patients in Saudi Arabia. However, most of these studies focused on the spectrum and antimicrobial sensitivity of the bacteria pathogens in neonatal sepsis [ 19 ], the impact of empiric antimicrobial therapy on the mortality of septic shock patients with liver cirrhosis [ 20 ], and pediatric ICU patients [ 21 ]. In addition, there is a lack of evidence on the adequacy of empiric antimicrobials provided to ICU sepsis patients and their determinants in Middle Eastern countries [ 22 ].…”
Section: Introductionmentioning
confidence: 99%